2018
DOI: 10.3390/ijms19010215
|View full text |Cite
|
Sign up to set email alerts
|

Protein Activity of the Fusarium fujikuroi Rhodopsins CarO and OpsA and Their Relation to Fungus–Plant Interaction

Abstract: Fungi possess diverse photosensory proteins that allow them to perceive different light wavelengths and to adapt to changing light conditions in their environment. The biological and physiological roles of the green light-sensing rhodopsins in fungi are not yet resolved. The rice plant pathogen Fusarium fujikuroi exhibits two different rhodopsins, CarO and OpsA. CarO was previously characterized as a light-driven proton pump. We further analyzed the pumping behavior of CarO by patch-clamp experiments. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 77 publications
7
45
0
Order By: Relevance
“…For instance, fungi are able to detect the ratio of different wavelengths of light to adjust to their surroundings, similar to phototropin‐mediated signalling in plants (Fuller, Loros & Dunlap, ; Fischer et al ., ; Schumacher, ). In many fungi, light can affect expression of genes, including those involved in important processes such as reproduction, morphogenesis, virulence and metabolism (Corrochano & Garre, ; Kamada et al ., ; Idnurm, ; Fuller et al ., ; Fischer et al ., ; Schumacher, ; Adam et al ., ; Wang et al ., ). Fungi possess well‐studied circadian clocks, too (Dunlap & Loros, , ; Liu & Bell‐Pedersen, ; Salichos & Rokas, ; Fuller et al ., ).…”
Section: Cellular Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fungi are able to detect the ratio of different wavelengths of light to adjust to their surroundings, similar to phototropin‐mediated signalling in plants (Fuller, Loros & Dunlap, ; Fischer et al ., ; Schumacher, ). In many fungi, light can affect expression of genes, including those involved in important processes such as reproduction, morphogenesis, virulence and metabolism (Corrochano & Garre, ; Kamada et al ., ; Idnurm, ; Fuller et al ., ; Fischer et al ., ; Schumacher, ; Adam et al ., ; Wang et al ., ). Fungi possess well‐studied circadian clocks, too (Dunlap & Loros, , ; Liu & Bell‐Pedersen, ; Salichos & Rokas, ; Fuller et al ., ).…”
Section: Cellular Complexitymentioning
confidence: 99%
“…These are not the only light‐sensitive proteins in fungi. Opsin‐like proteins in fungi are involved in regulation of the sexual cycle and in pathogenesis in some species, including Fusarium fujikuroi (Hypocreales) (García‐Martínez et al ., ; Adam et al ., ) and Blastocladiella emersonii (Blastocladiomycota) (Scheib et al ., ). Despite the ancient nature of this protein family, information about the biological roles of its members is still very fragmented.…”
Section: Cellular Complexitymentioning
confidence: 99%
“…The infected plants were grown for another 10 days with the programmed lighting and nutrient supply. Finally, the plant length and internodal distances were recorded, while the paler pigmentation of the bakanae disease was characterized and verified by measuring their content ratio of chlorophylls/carotenoids (Adam et al, 2018). Similar to the previously described experiment, the whole assay took around 2 weeks to evaluate the systemic F. fujikuroi infection of the rice plant in vivo (see Figure 1).…”
Section: Plant Infection Assaysmentioning
confidence: 99%
“…Adam et al analyzed a completely different aspect in the interaction of fungal pathogens with plants [ 10 ]. They found that phytopathogenic and phyto-associated ascomycetes contain rhodopsin-encoding genes.…”
Section: The Bad: Elucidating Mechanistic Strategies Of Plant Pathmentioning
confidence: 99%
“…While CarO was previously shown to be a light-driven proton pump, here the authors show that CarO is positively regulated by presence of indole-3-acetic acid and of sodium acetate. Intriguingly, they showed that deletion of the CarO-encoding gene from the genome of F. fujikuroi resulted in a hypervirulent strain with more severe bakanae symptoms than the reference strain, indicating that CarO has a role in attenuating the disease potential of the fungus [ 10 ]. Thus, although our knowledge on how plant pathogens infect host plants and on how the plants react to pathogen attack steadily increases, much remains still unknown.…”
Section: The Bad: Elucidating Mechanistic Strategies Of Plant Pathmentioning
confidence: 99%